Online Hate Speech and the Radical Right in Times of Pandemic: The Italian and English Cases - Caiani, Manuela; Carlotti, Benedetta; Padoan, Enrico (Javnost-The Public, 2021)
Social media is considered a particularly conducive arena for hate speech, a form of communication often linked to the radical right. The goal of this study is to offer an empirical contribution that comparatively explores the presence and features of hate speech in the social media discourse of the radical right (leaders and parties) in Italy and the UK during the first year of the pandemic. This mixed-methods study analyses 21,360 tweets using wordcloud analysis (to conceptually map the social media discourse of the radical right and mainstream parties), topic modelling (to identify the main topics of the radical right’s tweets and how they relate to Covid-19) and formalised content analysis (to better understand how hate speech is related to the virus). We find that radical right leaders have managed to bring exclusion-oriented issues to the agenda at this time of crisis, albeit in different ways, by emphasising different understandings of in-groups and out-groups in relation to Covid-19.